INTEGRASI CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS SYARIAH DALAM RITEL HEWAN KURBAN PERKOTAAN: STUDI LITERATUR INTEGRATIF - Nurdin, Nurdin; Kohar, Abdul (POLITEKNIK LP3I JAKARTA, 2026)
The development of the sacrificial animal (qurban) retail business in urban communities shows increasingly fierce competition, requiring businesses to be able to build long-term relationships with customers. Customer Relationship Management (CRM) is one strategic approach that can increase customer loyalty, but the implementation of CRM in sacrificial animal retail needs to be adapted to sharia values that emphasize honesty, trustworthiness, transparency, and worship-based service. This study aims to analyze the concept and application of Sharia-based Customer Relationship Management in the retail sale of sacrificial animals in urban communities through a literature review approach. The research method uses a systematic literature review of various scientific sources in the form of journals, books, and research reports relevant to the concepts of CRM, sharia marketing, and Muslim consumer behavior. The results of the study show that the application of sharia-based CRM not only focuses on customer satisfaction but also on building trust, religious commitment, and the value of sustainable transactions. Strategies such as personal communication, transparency regarding animal quality, ease of payment services, and assistance with sacrificial rituals have been proven to have the potential to increase customer loyalty and business differentiation. This study concludes that integrating CRM principles with sharia values can be a competitive advantage for sacrificial animal retailers in urban areas, while also strengthening the emotional and spiritual relationship between businesses and consumers. The implications of this study provide a conceptual basis for the development of an applicable sharia CRM model in the religious retail sector.